The Use of an In-Situ Measurement to Probe the Solidification Kinetics of Injection-Molded HDPE/PP Blends - Yang, Bin; Li, Gui-Jing; Yang, Ming-Bo; Su, Li-Feng; Miao, Ji-Bin; Xia, Ru; Chen, Peng; Deng, Shuang-Quan; Qian, Jia-Sheng (Journal of Research Updates in Polymer Science, 2013)
The largest portion of an injection molding (IM) cycle is actually occupied by the melt cooling stage, which also significantly dictates many end-use properties of the final parts, especially for crystalline polymers which undergo both solidification and crystallization processes simultaneously. The solidification kinetics of HDPE/PP blends were investigated under injection molding conditions with the aid of an in-situ measurement of in-cavity temperature profiles throughout the IM process. The obtained experimental results were in good agreement with our previous theoretical predictions. The present study will be instructive to the optimization of processing variables, and supplies good insight into the formation of various crystalline structures in injection-molded articles.